Potential of Trichoderma harzianum as Environmentally Friendly Natural Pesticides for Controlling Phytophthora in Duku Plants - Abdilla, Triyuni Verza; Simamora, Edenia Septefine; Amelia, Zahra Dini; Mulyani, Putri Dwi (Jurnal Biologi Tropis, 2025)
Duku fruit production in Jambi has begun to decline, one of the causes is stem cancer. This stem cancer disease is caused by the fungus Phytophthora sp. The symptoms caused by this disease are dry and soft bark like cork, wilted leaves and falling off until the tree finally dies. The purpose of this study was to isolate Phytophthora sp., characterize the morphology of the pathogen and test the ability of Trichoderma to inhibit the growth of Phytophthora sp. The research was conducted by calculating the percentage of inhibition starting from sampling the organs of the duku plant and continuing to the isolation stage. The antagonistic test of Phytophthora sp. against Trichoderma was carried out using the dual culture method (dual culture). The results showed that Phytophthora sp. can be obtained from the bark of plants, with characteristics of colonies that are textured like cotton, white in color, round in shape with uneven edges. Microscopic observation of fungal isolates showed that Phytophthora sp. has morphological characteristics in the form of round-oval conidia, non-septate mycelium and branched conidiophores. Trichoderma has the ability to inhibit the growth of Phytophthora sp. with an inhibitory power of 63.52%.